Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1161/atvbaha.112.254946
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Acidification Activates cAMP Responsive Element Binding Protein via Na+/H+ Exchanger Isoform 1–Mediated Ca 2+ Oscillation in Central Nervous System Pericytes

Abstract: The online-only Data Supplement is available with this article at http://atvb.ahajournals.org/lookup/suppl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…Under the culture conditions employed, spontaneous Ca 2+ oscillations were not observed, whereas a spontaneous transient rise in Ca 2+ was only occasionally encountered. Finally, considering that extracellular acidosis induces Ca 2+ oscillations [22] , we confirmed that pH of the culture medium was not changed after the addition of butyrate (medium pH = 7.21, medium + sodium butyrate pH = 7.26, conditions: 37°C and 5% CO 2 ).…”
Section: Resultssupporting
confidence: 70%
“…Under the culture conditions employed, spontaneous Ca 2+ oscillations were not observed, whereas a spontaneous transient rise in Ca 2+ was only occasionally encountered. Finally, considering that extracellular acidosis induces Ca 2+ oscillations [22] , we confirmed that pH of the culture medium was not changed after the addition of butyrate (medium pH = 7.21, medium + sodium butyrate pH = 7.26, conditions: 37°C and 5% CO 2 ).…”
Section: Resultssupporting
confidence: 70%
“…In addition to AMPK, activated CaMKKβ phosphorylates and activates CaMK1 (Thr177) (Figure 4D). This is a key observation as in addition to PKA, CREB (ser133) can be phosphorylated by CaMK1 [37], [38], as seen in Figure 4D and E. Although such serine phosphorylation of CREB could also result from the small observed increase in cAMP, inhibition of CaMKKβ, and thereby CaMK1, with the CaMKKβ inhibitor STO-609 (further discussed below) also inhibited phosphorylation of CREB (Figure S2), indicating that it is dependent on CaMKKβ activity.…”
Section: Resultsmentioning
confidence: 74%
“…4). Among possible factors produced by PDGFRb -positive cells, we focused on IL6 because it can be produced from mesenchymal cells, including pericytes (Gaceb et al, 2018), and can induce the phosphorylation of STAT3 and AKT, both potent intracellular transducers of activation and survival/proliferation of astrocytes (Yamashita et al, 2005;Nakamura et al, 2012;Wanner et al, 2013;Gu et al, 2016). It is also reported that IL6 can induce poststroke angiogenesis and repair (Gertz et al, 2012).…”
Section: Discussionmentioning
confidence: 99%